Synthesis of Mannich Base of 2, 3-Diphenyl 7(H) Oxofuro (3, 2-g) (I) Benzopyrones as Possible Biological Active Agents - Rajitha, B.; Vijayalakshmi, J.; Kanakalingeshwar Rao, M. (Asian Journal of Chemistry, 2010)
Synthesis of 2, 3-diphenyl 7(H) oxofuro (3, 2-g) (1) benzopyrone (III), 6(alkyl/aryl aminomethyl)-5-hydroxy 7(H) oxofuro (3, 2-g) (1) benzopyrone (IV a-f) and its Mannich bases is reported as possible biologically active compounds.